Stato dell’arte e novità sul trattamento delle fratture esposte - Comitini, S.; Berti, M.; Ganci, M.; Amendola, L.; Commessatti, M.; Barca, P.; Grippo, G.; Tigani, D.S. (Lo Scalpello - Journal, 2019)
OPEN FRACTURES: CLASSIFICATION, MANAGEMENT AND INNOVATIVE DEVICESOpen fractures management has always been one of the main challenges in traumatologic surgery: definition of themost appropriate therapeutic protocol is a research and debate topic. Infectious risk minimisation, soft-tissue damageresolution, fracture reduction and fixation are the main objectives in order to recover anatomical and functionalintegrity of the involved district. Management protocols are characterized by the contrast between an early total careapproach and a gradual damage control approach.Gustilo-Anderson classification is still the most widely used in order to set open fractures management, but itslimitations have led to the development of other important classifications.This article, through a literature review, aims at summarising main classifications and state of the art on openfractures treatment and at highlighting latest protocols and technical solutions adopted: negative wound pressiontherapy, antibacterial coated nails and other innovative devices.